Speaking games B1 - C1 : photocopiable activities to make language learning fun - Anderson, Jason, ....- (Surrey : Delta Publishing, 2014)
From the author of Role Plays for Today and Teamwork, Speaking Games is a new photocopiable resource book of 50 speaking games for teachers of English to use in class with both adult and teenage learners at levels B1-C1. It provides teachers with original, effective and enjoyable activities that focus on developing the learners' ability to use language confidently in real-world situations. It includes a wide variety of activities which get learners speaking on topics of interest while injecting energy, fun and motivation into a class. Each game: is easy to print, use and recycle; is presented in a double-page spread of instructions and resources; includes a 'Rules of the Game' handout, to be used as an authentic reading opportunity Speaking Games is divided into four sections: Board Games - photocopiable boards for games such as Snakes and Ladders or Scrabble; Card Games - photocopiable cards that are cut up and used either as questions or prompts; Secrets and Lies - activities that involve either guessing secret information or guessing whether a speaker is being honest or not; and, Quizzes, Puzzles and Challenges - including well-known quiz show formats, such as Who Wants to Be a Millionaire, problem solving puzzles, brainteasers and activities that challenge learners to use language accurately while speaking fluently.
Keywords: Engels ; didactiek